An integrated simulation with design on experiment approach for shop floor improvement solution selections - Low, S.-N. (Inderscience Publishers, 2016)
This paper highlights the decision process of evaluating and selecting shop floor improvement solution by integrating design of experiment (DOE) in a discrete event simulation (DES) environment. In this study, the approach is tested and verified using an improvement project of a case study. The simulated data from the basic simulation model were verified by comparing with the current production data of real scenarios through statistical t- Test. Once it been verified, the basic simulation model were then only been modified according to the various proposed improvement solution. The most promising improvement solutions suggested reducing the 20 number of operators while increasing the 21.86 utilisation of operators in the system. Findings from the paper indicate that simulation with the DOE method can be used to assist in decision-making regarding the improvement alternatives of production system. It was useful in achieving continuous improvement in the manufacturing industry. Â© Copyright 2016 Inderscience Enterprises Ltd.